Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

What is the result of subtracting the second equation from the first?
x - 3y = 6
−8x−y = 6



Sagot :

Answer:

9x - 2y = 0

Step-by-step explanation:

[tex](x - 3y) - ( - 8x - y) = 6 - 6 \\ \\ x - 3y +8 x + y = 0 \\ \\ x + 8x + y - 3y = 0 \\ \\ 9x - 2y = 0[/tex]

We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.